2004
DOI: 10.1191/0748233704th201oa
|View full text |Cite
|
Sign up to set email alerts
|

Urinary nickel: measurement of exposure by inductively coupled plasma argon emission spectrometry

Abstract: Nickel is a rare earth metal and is widely used in modern industry. Its overexposure in human beings can provoke significant effects including lung, cardiovascular and kidney diseases. As an index of occupational exposure, urine is widely used for the monitoring of nickel concentration because it is a minimally invasive method. Recent studies have used atomic absorption spectrometry to measure nickel concentration. In this study, we introduced novel inductively coupled plasma argon emission spectrometry (ICPAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…After oral administration of Nickel, no renal failure was detected (Koizumi et al 2005), the increase in urinary Nickel concentration occurred in a dose dependent manner, and soluble Ni compounds were excreted with urine within 72 hours after a single oral administration (Ishimatsu et al, 1995;Koizumi et al 2005;Janicka and Cempel, 2003). This is confirmed by Nielsen et al, (1993) who reported that up to 20 h after single oral administration of doses comparable to the human dietary intake, Nickel retention was highest in the kidneys.…”
Section: Metabolism and Eliminationmentioning
confidence: 99%
“…After oral administration of Nickel, no renal failure was detected (Koizumi et al 2005), the increase in urinary Nickel concentration occurred in a dose dependent manner, and soluble Ni compounds were excreted with urine within 72 hours after a single oral administration (Ishimatsu et al, 1995;Koizumi et al 2005;Janicka and Cempel, 2003). This is confirmed by Nielsen et al, (1993) who reported that up to 20 h after single oral administration of doses comparable to the human dietary intake, Nickel retention was highest in the kidneys.…”
Section: Metabolism and Eliminationmentioning
confidence: 99%
“…[3-5] Nickel is typically absorbed in the lungs or gastrointestinal tract, with the main excretion occurring in urine. [9, 10]…”
Section: Introductionmentioning
confidence: 99%
“…7,8 People are principally exposed to nickel through skin contact with nickel containing jewelry, consumption of foods (e.g., chocolate, nuts, and oatmeal), and industrial exposures such as battery production, alloy production, or stainless steel welding. 9,10 As one of the main components in metal-onmetal hip and knee implants, nickel from erosion of implant materials can be a source of exposure in people with these implants. [3][4][5] Nickel is typically absorbed in the lungs or gastrointestinal tract, with the main excretion occurring in urine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of nickel is performed by several techniques such as x-ray absorption spectroscopy [15], flame and electro thermal atomic absorption spectrometry [16][17][18][19][20], atomic emission spectrometry [21], spectrophotometry [22,23] and fluorescence spectroscopy [24]. Among the methods, spectrophotometric methods offer many appealing characteristics including: simple instrumentation, rapid response times and easy operation.…”
Section: Introductionmentioning
confidence: 99%